Talking Map as a data production instrument in qualitative research (Research, Society and Development, 2020)
This work aims to describe the development of the Talking Map in participatory research with undergraduate nursing students on the concept of health promotion. This is an experience report on the use of the Talking Map as a data production technique in Participatory Health Research, an innovative approach in the preparation of monographs, dissertations and theses. The research field was the Aurora de Afonso Costa Nursing School and the data were produced from August to December 2019. Participants were asked to respond in a playful way, on cardboard, "what is it about the Nursing School that favors the Health Promotion of undergraduate students?”. Subsequently, they answered on another cardbord “what would you like to have at the Nursing School to favor the Health Promotion of undergraduates?”. From the findings, three categories emerged: Health Promotion Actions at EEAAC/UFF; Interpersonal Relations at EEAAC/UFF and The promoting environment EEAAC/UFF.  Therefore, it is concluded that the Talking Map stimulated the participants to reflect and be creative, providing well-being during the research. Proved to be effective as an instrument, capable of extracting from Nursing students information about the concept of health promotion, favoring the achievement of objectives. Thus, it contributed to a collective construction of the findings.